DETERMINING ALTERNATIVE PATHWAYS TOWARDS GRAIN YIELD IN 32 VARIETIES OF COWPEA (VIGNA UNGUICULATA) (L) WALP.) - AMUJOYEGBE , B. J.; OBISESAN, I. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Thirty-two varieties of cowpea were evaluated for variation in seeding, phenological and grain yield characters over two seasons. Seedling traits contributed only to crop establishment and affected phenological traits but had no effect yield. Phenological traits affected yield either positively or negatively as prolonged days-to-seed-fill favoured increased grain yield while protracted growth duration favours biomass accumulation but decreases yield. Twelve varieties had significant high grain yields (above 1000 kg/ha) while six had stable yield in both seasons but five varieties exhibited significant genotype X environment interactions (G x E) for grain yield. Days-to-physiological maturity (DPM) and days-to harvest maturity (DHM) showed positive significant correlation with grain yield among the high grain yielding varieties while all the phenological traits showed negative effect on the by yielding varieties. All the growth rates measurements contributed significantly to grain yield as they showed positive significant correlation to grain yield on all the 32 varieties of cowpea. Yield growth rate (YGR) had the highest significant association with grain yield both among the high yielding varieties (0.965) and yielding varieties (0.707). Path analysis shoved that YGR was the most important determinant of grain yield of an the traits investigated